A stabilized peptide ligand for multifunctional glioma targeted drug delivery - Ying, Man; Shen, Qing; Zhan, Changyou; Wei, Xiaoli; Gao, Jie; Xie, Cao; Yao, Bingxin; Lu, Weiyue (Journal of controlled release, 2016)
Peptide ligands consisting of l-amino acids are subject to proteolysis in vivo. When modified on the surface of nanocarriers, those peptide ligands would readily degrade and the targeting efficacy is significantly attenuated. It has received increasing scrutiny to design stable peptide ligands for targeted drug delivery. Here, we present the design of a stable peptide ligand by the formation of a head-to-tail amide bond as an example. Even though the linear l-peptide A7R (termed LA7R) can bind specifically to vascular endothelial growth factor receptor 2 (VEGFR2) and neuropilin-1 (NRP-1) that are overexpressed on glioma cells, neovasculature and glioma vasculogenic mimicry (VM), the tumor-homing capacity of LA7R is greatly impaired in vivo due to proteolysis (e.g. in the serum). A cyclic A7R (cA7R) peptide was identified by computer-aided peptide design and synthesized with high yield by combining solid phase peptide synthesis and native chemical ligation. The binding of cA7R to both receptors was theoretically and experimentally assessed. In our simulated model hydrophobic and ionic interactions dominated the binding of LA7R to receptors. It is very interesting that cA7R adopting a different structure from LA7R retained high binding affinities to receptors without affecting the hydrophobic and ionic interactions. After head-to-tail cyclization by the formation of an amide bond, cA7R exhibited exceptional stability in mouse serum. Either cA7R or LA7R was conjugated on the surface of doxorubicin (DOX) loaded liposomes (cA7R-LS/DOX or LA7R-LS/DOX). The results of in vitro cellular assays indicated that cA7R-LS/DOX not only displayed stronger anti-proliferative effect against glioma cells, but also demonstrated to be more efficient in destruction of VM and HUVEC tubes in comparison to LA7R-LS/DOX and plain liposomes (LS/DOX, without peptide conjugation). cA7R conjugation could achieve significantly higher accumulation of liposomes in glioma than did LA7R conjugation, which in turn, cA7R-LS/DOX could substantially suppress subcutaneous tumor growth when compared with other DOX formulations (free DOX, LS/DOX and LA7R-LS/DOX). The designed cyclic A7R exhibited the capability of targeting glioma cells, neovasculature and VM simultaneously in vivo. Considering the ease of synthesis, high binding affinity to receptors and increased stability of cA7R peptide in the present study, the design of head-to-tail cyclized peptides by the formation of amide bond based on computer-aided peptide design presents an alternative method to identify proteolytically stable peptide ligands. [Display omitted]